THE FRAMING OF INTERNATIONAL MEDIA ON ISLAM AND TERRORISM - Yusof, Sofia Hayati; Hassan, Fauziah; Hassan, Md Salleh; Osman, Mohd Nizam (European Scientific Journal, ESJ, 2013)
The role of media is to shape opinions and presenting a particular version as reality. They also play an important role in structuring the audience perspectives about the issues that happen around the world. For this matter, they are believed and expected to portray a fair picture on any issues occur both at the local and international level. However, in portraying Islam, especially after the September 11 attacks, a number of research found that the International media tend to negatively depict Islam by associating it with terrorism. Issues concerning the way international media, specifically in the US and UK, equate Islam with terrorism have been tremendously debated. Research showed that after the September 11 attack, terrorism has been repeatedly associated with Islam by most of the international media. There is a perception that international media play a vital role in creating a relationship between Islam and terrorism in their media that leads to the formation of labels on Islam and terrorism. However, many think that the death of Osama Bin Laden would end the negative association between Islam and terrorism made by Western media for so many years after Sept 11. Based on this view, the researchers will be conducting a content analysis on two international news magazines looking at the tendency patterns in labeling Islam associated with terrorism after the death of Osama Bin Laden and also looking at the discourse analysis by extracting any recurrent themes emerged from the articles selected.